1999
DOI: 10.1029/1999wr900147
|View full text |Cite
|
Sign up to set email alerts
|

Slow two‐phase flow in artificial fractures: Experiments and simulations

Abstract: Abstract. The slow displacement of a wetting fluid by a nonwetting fluid in models of a single fracture was studied experimentally and by computer simulations on identical geometries. The fracture was modeled by the gap between a rough plate and a smooth transparent plate, both oriented horizontally. Two different rough plates were used, a textured glass plate and a polymethyl methacrylate plate with a computer-generated pattern. A nonwetting fluid (air) was injected slowly through an inlet into the model and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
35
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 23 publications
2
35
0
1
Order By: Relevance
“…Slow drainage in fractures has been the subject of several studies (see Glass et al 2001, and references therein). Amundsen et al (1999) studied slow drainage in two artificial fractures, one with a discrete self-affine aperture field (model A) and the other with a continuous aperture field, which was self-affine only below the typical size of main "valleys" (model B). It seems that these fractures were well connected, i.e., the contact fractional area between top and bottom plates was very small or null.…”
Section: Introductionmentioning
confidence: 99%
“…Slow drainage in fractures has been the subject of several studies (see Glass et al 2001, and references therein). Amundsen et al (1999) studied slow drainage in two artificial fractures, one with a discrete self-affine aperture field (model A) and the other with a continuous aperture field, which was self-affine only below the typical size of main "valleys" (model B). It seems that these fractures were well connected, i.e., the contact fractional area between top and bottom plates was very small or null.…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, in a heterogeneous and particularly rough fracture, the correlation length of the aperture can sometimes be finite and much smaller than the mean aperture. In this case, it was shown that the capillary pressure is mainly controlled by the aperture, leading to an invasion percolation process (Glass et al 1998;Amundsen et al 1999). Several experiments were performed (Nicholl et al 1994) to study the downward water infiltration through dried or partially dried fracture.…”
mentioning
confidence: 98%
“…Most of the studies concern water-air density driven flows (Nicholl and Glass 2005;Amundsen et al 1999). In the present paper, we study experimentally the upward vertical invasion of oil in a fracture where the fluid initially in place is a wetting fluid of higher density.…”
mentioning
confidence: 99%
“…Under the influence of gravity force of DNAPL, it migrates downward through unsaturated zone. DNAPL must have sufficient mass to overcome the capillary forces of smaller pores holding water (Amundsen et al, 1999;Ji et al, 2008). Therefore, DNAPL tends to remain behind while it is migrating to water table, trapped in unsaturated zone.…”
Section: Introductionmentioning
confidence: 99%